2014
DOI: 10.4049/jimmunol.1303067
|View full text |Cite
|
Sign up to set email alerts
|

Tyk2-Dependent Bystander Activation of Conventional and Nonconventional Th1 Cell Subsets Contributes to Innate Host Defense against Listeria monocytogenes Infection

Abstract: IL-12, which is produced in response to intracellular bacteria, such as Listeria monocytogenes, promotes the development of pathogen-specific Th1 cells that play an important role in host defense. However, it has also been known that CD44high memory-phenotype CD4 T cells with Th1 functions naturally occur in naive mice, and that lymphopenia-induced proliferation of naive CD4 T cells generates memory-phenotype CD4 T cells with Th1 functions, although their differentiation mechanism and contribution to host defe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…These results suggested that TYK2 promoter variant may serve as a virus-induced T1D susceptibility gene, possibly due to reduced type 1 IFN response ( Nagafuchi et al, 2015 ), but not Th1 cell-dependent autoimmunity. Consistently, it was reported that Tyk2 -mediated signaling was not essential for the development of Th1 cell ( Hashiguchi et al, 2014 ). TYK2 promoter variant serves as a risk not only in T1D but also in T2D, suggesting that TYK2 promoter variant is associated with an overall risk for diabetes ( Nagafuchi et al, 2015 ).…”
Section: Introductionsupporting
confidence: 70%
“…These results suggested that TYK2 promoter variant may serve as a virus-induced T1D susceptibility gene, possibly due to reduced type 1 IFN response ( Nagafuchi et al, 2015 ), but not Th1 cell-dependent autoimmunity. Consistently, it was reported that Tyk2 -mediated signaling was not essential for the development of Th1 cell ( Hashiguchi et al, 2014 ). TYK2 promoter variant serves as a risk not only in T1D but also in T2D, suggesting that TYK2 promoter variant is associated with an overall risk for diabetes ( Nagafuchi et al, 2015 ).…”
Section: Introductionsupporting
confidence: 70%
“…This idea is supported by the findings that NK cells produce considerable amounts of IFN-g upon i.p. L. monocytogenes infection (73)(74)(75)(76) and modestly reduce bacterial burden upon transfer into Ifng 2/2 mice (77) and upon local infections (62,78). Increased sensitivity of Tyk2 DNK mice to L. monocytogenes infection correlated with an impaired IFN-g production by NK cells, supporting the notion that the balance between IFN-g-and IL-10-producing NK cells critically determines their role in antibacterial immunity (79,80), thus arguing against a previously suggested negative impact of NK cellderived IFN-g (72).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, IL-12 promotes IFN-γ-dependent neutrophil recruitment into the lungs of mice after intranasal infection with S. pneumonia (Sun et al, 2007). Specifically, IL-12 and IFN-γ induce synergistically bacterial clearance from the lungs and pulmonary cellular infiltration during extracellular and intracellular bacterial infection, such as L. monocytogenes, S. pneumonia, Chlamydia muridarum, M. tuberculosis (Haring et al, 2005; Mpiga and Ravaoarinoro, 2006; Sun et al, 2007; Cooper and Khader, 2008; Jupelli et al, 2010; Hashiguchi et al, 2014). More importantly, Il-12a, Il-12b, Il-2, Ifn- γ are up-regulated in bovine lungs by an intratracheal P. multocida inoculation (Mathy et al, 2002), which suggest that Th1 responses are induced by P. multocida and there are some similarities between mice and cattle during P. multocida infection by an intratracheal or intraperitoneal route.…”
Section: Discussionmentioning
confidence: 99%